Expression of Drosophila melanogaster V-ATPases in Olfactory Sensillum Support Cells - Kalpana Jain; Sinisa Prelic; Bill S. Hansson; Dieter Wicher (Insects)
V-ATPases are ubiquitous and evolutionarily conserved rotatory proton pumps, which are crucial for maintaining various biological functions. Previous investigations have shown that a V-ATPase is present in the support cells of moth trichoid sensilla and influences their olfactory sensory neuron performance. Generally, V-ATPases are thought to regulate the pH value within the sensillum lymph, and aid K+ homeostasis within the sensillum. This, in turn, could influence various mechanisms involved within the support cells, like maintaining the receptor membrane potential (receptor current), nutrient and ion transport, odorant solubility, and various signaling mechanisms. In this study, we identify V-ATPase expression and localization in the Drosophila melanogaster antenna using bioinformatics and immunohistochemistry. Elucidating an olfactory V-ATPase function will improve our current understanding of how support cells contribute to Drosophila’s sense of smell.